IDENTIFICATION AND DIFFERENTIATION OF THE ASIAN ELEPHANT IVORY BY USING SCHREGER LINES (Journal of Institute of Science and Technology, 2017)
Elephant ivory is one of the highly priced, illegally traded wildlife trophies and its identification has always been a challenging task. A total of 21 Asian elephant tusks stored at the office of the Chitwan National Park, Kasara, Nepal were morphometrically studied with an aim to typify elephant ivory by using Schreger lines. The ivory samples were cleaned, their Schreger lines were photographed and their angles were measured by using a protractor. A total of 120 Schreger angles data from both outer and inner areas were obtained resulting both concave and convex appearance. The observed maximum and minimum Schreger angles values were 125° and 50° respectively. The mean Schreger angle was found to be 95.60° (±14.23). The Schreger lines were present in all studied samples. Thus, it is concluded that the presence of Schreger line is the identifying feature of an elephant tusk.Journal of Institute of Science and TechnologyVolume 22, Issue 1, July 2017, Page: 99-103